Blindness from quinine toxicity. Issue 3 (March 1988) - Bacon, P; Spalton, D J; Smith, S E
Abstract : We report a case of quinine overdose in a 47-year-old man who presented with blindness. Fundus photography demonstrates the acute and subsequent retinal changes, and his visual recovery to normal acuity with visual field constriction is documented. Pupillary and electrodiagnostic findings are recorded. Stellate ganglion block has been widely advocated as a helpful therapeutic measure, but out patient was treated with a unilateral stellate ganglion block without apparent benefit to that eye. From a review of the literature we believe that quinine produces its effects by toxicity on the retina rather than by vasoconstriction and that stellate ganglion block probably does not alter the natural history of the retinal toxicity.